THE APPLICATION OF RECIPROCAL TEACHING TO IMPROVE BUSINESS TEXT READING COMPREHENSION OF BUSINESS ADMINISTRATION STUDENTS OF BENGKALIS STATE POLYTECHNIC - A Malik; Aswandi Aswandi (Politeknik Negeri Bengkalis, 2019)
Based on the problems found in the classroom, the students at State Polytechnic of Bengkalis had problems in comprehending business texts. It seemed difficult for them to understand contents and to identify the inference of the text. They also had limited vocabulary. Therefore, the researcher decided to solve these problems by applying Reciprocal Teaching. The researchaimedat finding out to what extent Reciprocal Teaching could improve the students’ reading comprehension of business texts. This reciprocal teaching applicationresearch was conducted in two cycles. Each cycle consisted of four meetings; three meetings for teaching reading comprehension of business texts and one meeting was for the test. Participants of the research were 25 students of Business Administration major. There were some instruments used asdata collection were (1) observation sheets; students, teacher, and teaching steps (2) field notes (3) and reading comprehension tests.The research findings showed that Reciprocal Teaching could improve the students’ reading comprehension of business texts. It could be seen from the improvement of the students’ score in reading comprehension of Business texts test. The average score of students in cycle 1 was 63,36 and in cycle 2 was 67,68. In conclusion, the implementation of Reciprocal Teaching could improve the students’ reading comprehension of Business texts at Business administration Students of State Polytechnic of Bengkalis. It improved both students’ score in reading tests and their interest in reading activities.